Perancangan Perabot Kerja Kantor untuk Menjembatani Gap Generation dan Mencegah Sick Building Syndrome - Andre Halim (Intra, 2017)
Working in office buildings over a long period of time is intended for the benefit of increasing the productivity of each employee, but it does not mean that the harmony factor of social relations and health can be ignored. Workers in the offices consist of four generations that can cause gaps in various factors, affecting the environment and working environment other than the work environment contaminated by various radiation factors resulting in Sick Building Syndrome (SBS). Formulation of existing problems in this design is a model of office furniture design that can bridge the Gap Generation and office furniture design model that can prevent Sick Building Syndrome. This design uses Design Thinking Life skills Enrichment design thinking method by Ian Tan consisting of 6 stages namely discovery, interpretation, ideation, experimentation, evaluate, and implementation. These factual and actual conditions need to be prevented through the design of office furniture, which can be used by generations and accommodate all the activities of each generation. Other results of the design of office furniture can be a reference to improve air quality and awaken the public to always maintain health in every area and facility used on the move. For this purpose to be achieved, the design is made in the form of a set of office work desk furniture, for 1 person, work together, living room table, and conference table with additional facilities for sansiviera plant placement.